ANALISIS KEBUTUHAN DAN PENCARIAN INFORMASI IBU DENGAN KELAHIRAN ANAK PERTAMA PERIODE POSTPARTUM: STUDI KASUS WHATSAPP GROUP ZONA MAMA - Subekti, Aji (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2019)
This study aims to understand the needs and search for information from primiparous mothers, so that they can provide appropriate information and certainly can reduce maternal anxiety towards postpartum depression. The research method used is a case study on WhatsApp Group (WAG) Zona Mama. The result is that there is concern and anxiety from primiparous mothers in the postpartum phase. This happens because of a lack of information about topics such as breastfeeding, how to care for children, and complementary feeding provided by information providers such as health workers and librarians. Information searching that has been done so far using an active scanning model that is carrying out active information retrieval, but does not have a detailed plan. Therefore, it seems that information leaflets from information providers such as hospitals and libraries are needed by new mothers. Sometimes websites and forums are doubtful by mothers. They need an information center that is consistent and controlled by professional.